Characterizing depth-dependent refractive index of articular cartilage subjected to mechanical wear or enzymic degeneration - Wang, K.; Wu, Jian-Ping; Day, R.; Kirk, Brett; Hu, X. (SPIE, 2016)
Utilizing a laser scanning confocal microscope system, the refractive indices of articular cartilage (AC) with mechanical or biochemical degenerations were characterized to investigate whether potential correlations exist between refractive index (RI) and cartilage degeneration. The cartilage samples collected from the medial femoral condyles of kangaroo knees were mechanically degenerated under different loading patterns or digested in trypsin solution with different concentrations. The sequences of RI were then measured from cartilage surface to deep region and the fluctuations of RI were quantified considering combined effects of fluctuating frequency and amplitude. The compositional and microstructural alterations of cartilage samples were assessed with histological methods. Along with the loss of proteoglycans, the average RI of cartilage increased and the local fluctuation of RI became stronger. Short-term high-speed test induced little influence to both the depth fluctuation and overall level of RI. Long-term low-speed test increased the fluctuation of RI but the average RI was barely changed. The results substantially demonstrate that RI of AC varies with both compositional and structural alterations and is potentially an indicator for the degeneration of AC.